Heterogeneous vesicles in mucous epithelial cells of posterior esophagus of Chinese giant salamander (Andrias davidianus) - H. Zhang; X. Guo; S. Zhong; T. Ge; S. Peng; P. Yu; Z. Zhou (European Journal of Histochemistry, 2015)
The Chinese giant salamander belongs to an old lineage of salamanders and endangered species. Many studies of breeding and disease regarding this amphibian had been implemented. However, the studies on the ultrastructure of this amphibian are rare. In this work, we provide a histological and ultrastructural investigation on posterior esophagus of Chinese giant salamander. The sections of amphibian esophagus were stained by hematoxylin & eosin (H&E). Moreover, the esophageal epithelium was observed by transmission electron microscopy (TEM). The results showed that esophageal epithelium was a single layer epithelium, which consisted of mucous cells and columnar cells. The esophageal glands were present in submucosa. The columnar cells were ciliated. According to the diverging ultrastructure of mucous vesicles, three types of mucous cells could be identified in the esophageal mucosa: i) electron-lucent vesicles mucous cell (ELV-MC); ii) electron-dense vesicles mucous cell (EDV-MC); and iii) mixed vesicles mucous cell (MV-MC).